Copper hypersensitivity - Fage, Simon W.; Faurschou, Annesofie; Thyssen, Jacob P. (Contact dermatitis, 2014)
The world production of copper is steadily increasing. Although humans are widely exposed to copper‐containing items on the skin and mucosa, allergic reactions to copper are only infrequently reported. To review the chemistry, biology and accessible data to clarify the implications of copper hypersensitivity, a database search of PubMed was performed with the following terms: copper, dermatitis, allergic contact dermatitis, contact hypersensitivity, contact sensitization, contact allergy, patch test, dental, IUD, epidemiology, clinical, and experimental. Human exposure to copper is relatively common. As a metal, it possesses many of the same qualities as nickel, which is a known strong sensitizer. Cumulative data on subjects with presumed related symptoms and/or suspected exposure showed that a weighted average of 3.8% had a positive patch test reaction to copper. We conclude that copper is a very weak sensitizer as compared with other metal compounds. However, in a few and selected cases, copper can result in clinically relevant allergic reactions.